1990
DOI: 10.1002/pssa.2211210223
|View full text |Cite
|
Sign up to set email alerts
|

IR Absorption Spectra of SiO2 Films Grown by Photo-CVD

Abstract: The infrared absorption spectra of photo‐CVD grown SiO2 are investigated. By virtue of the low temperature growth, the stress at the SiSiO2 interface is absent in these films as shown by the absorption spectra. An attempt is made to infer the structure of these films on the basis of results of IR spectra, etching rate, and refractive index measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Both peak maxima show minor frequency shifts of a few wavenumbers as a function of the layer thickness and also between the different precursors, but the overall shape of this band remains essentially unchanged from the native oxide layer (spectra (0/0) up to 23 deposited SiO 2 layers (spectra 23/23), regardless of the particular precursor. Since the ν(SiO) peak shape and frequency are known to respond very sensitively to changes in the composition and structure of the SiO 2 film, it may be concluded that this deposition process produces amorphous, “native-like” silicon oxide regardless of the type and structure of the alkylsiloxane precursor film. The ν(SiO) band intensities in Figure , therefore, lack any specific structural or orientational contributions (contrary to the ν(CH) intensities, for example) and can be used as a second, independent measurein addition to the ellipsometric data of Figure for the thickness of the oxide film.…”
Section: Resultsmentioning
confidence: 99%
“…Both peak maxima show minor frequency shifts of a few wavenumbers as a function of the layer thickness and also between the different precursors, but the overall shape of this band remains essentially unchanged from the native oxide layer (spectra (0/0) up to 23 deposited SiO 2 layers (spectra 23/23), regardless of the particular precursor. Since the ν(SiO) peak shape and frequency are known to respond very sensitively to changes in the composition and structure of the SiO 2 film, it may be concluded that this deposition process produces amorphous, “native-like” silicon oxide regardless of the type and structure of the alkylsiloxane precursor film. The ν(SiO) band intensities in Figure , therefore, lack any specific structural or orientational contributions (contrary to the ν(CH) intensities, for example) and can be used as a second, independent measurein addition to the ellipsometric data of Figure for the thickness of the oxide film.…”
Section: Resultsmentioning
confidence: 99%